Soil and agricultural capability of UiTM Sarawak Campus farm, Malaysia - Mohidin, Hasmah; Jack, Radziah; Man, Sulaiman; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2009)
An area of 40.5 ha at UiTM Sarawak, Samarahan Campus farm was surveyed at a detailed level. There are three soil major groups, three soil families and six soil series identified in UiTM Sarawak, Samarahan campus. The three soil major groups are Red Yellow Podzolic (RYP), Gley and Organic. The three soil families are BEKENU and MERIT Family of RYP Group, BIJAT and TATAU Family of Gley Group and ANDERSON Family of Organic group. The soil series identified are Bekenu of BEKENU Family, Merit and Jakar of MERIT Family, Daro of BIJAT Family, Tatau of TATAU Family and Gadong of ANDERSON Family. The majority of the area is classified as having agriculture capability of Class 2t, 3te and 4te. Class 2t, 3te, 4te consist of Jakar, Merit and Bekenu series and which are restricted for agriculture due to the steepness of the slope. Class 3wi consists of Daro series soil where wetness and inundation hazard is a moderate limitation for agriculture use. Class 4fw consists of Tatau series soil which is not suitable for agriculture used due to serious fertility and serious wetness. Class 04go consists of Gadong series which is also not suitable for agricultural use due to high groundwater table and undecomposed organic surface layer.